Green growth, economic development, and carbon dioxide emissions: an evaluation based on cointegration and vector error correction models - Sun, Yu; Li, Mingxing; Sun, Hongzheng; Kanwel, Shahida; Zhang, Mengjuan; Erum, Naila; Hussain, Abid (MDPI, 2022)
Economic development is mainly dependent on fossil fuels. The massive use of fossil fuels has led to changes in the climate environment, in which the deterioration of air quality has affected people’s daily lives. This paper introduces the green growth level as a control variable to explore the connection between carbon dioxide emissions and the level of economic growth. It uses the EKC algorithm and VEC model to analyze Nanjing city’s data from 1993 to 2018. Given the data availability, the ARIMA algorithm was used to project carbon emissions for 2019–2025. It is found that the EKC curve of Nanjing City shows an N-shape, and the growth of economic level will cause the enhancement of carbon dioxide emissions. Carbon emissions will reach 7,592,140 tons in 2025. At present, we are in an essential stage of transition from N-shape to inverted U-shape, and this paper makes several recommendations based on the findings.
Keywords: economic development level; carbon dioxide emissions; autoregressive integrated moving average (ARIMA) model; environmental Kuznets curve (EKC) model; vector error correction (VEC) model